BRIDGING REASON AND REVELATION IN TRADITIONAL ISLAMIC EDUCATION - Laila Salma (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study explores the integration of reason (ʿaql) and revelation (naql) within the framework of traditional Islamic education. While modern science emphasizes empirical knowledge and rational inquiry, Islamic education has historically rooted itself in divine revelation and classical scholarship. The research investigates how traditional Islamic institutions can bridge these two epistemological domains, promoting a holistic educational model that nurtures both intellectual and spiritual growth. Using a qualitative approach, this study examines curriculum practices, pedagogical models, and educator perspectives to understand the challenges and opportunities in harmonizing scientific reasoning with religious values. The findings highlight that integration is not only possible but essential in shaping learners who are intellectually competent and spiritually grounded. This research contributes to the discourse on educational reform by proposing pathways for meaningful dialogue between faith-based traditions and contemporary knowledge systems.